Modeling of H1N1 outbreak in Rajasthan: Methods and approaches - Shiv Dutt Gupta; Vivek Lal; Rohit Jain; Om Prakash Gupta (Wolters Kluwer Medknow Publications, 2011)
Background: Mathematical models could provide critical insights for informing preparedness and planning to deal with future epidemics of infectious disease. Objective: The study modeled the H1N1 epidemic in the city of Jaipur, Rajasthan using mathematical model for prediction of progression of epidemic and its duration. Materials and Methods: We iterated the model for various values of R 0 to determine the effect of variations in R 0 on the potential size and time-course of the epidemic, while keeping value of 1/g constant. Further simulation using varying values of 1/g were done, keeping value of R 0 constant. We attempted to fit the actual reported data and compared with prediction models. Results: As R 0 increases, incidence of H1N1 rises and reaches peak early. The duration of epidemic may be prolonged if R 0 is reduced. Using the parameters R 0 as 1.4 and 1/g as 3, it estimated that there would have been 656 actually infected individuals for each reported case. Conclusion: The mathematical modeling can be used for predicting epidemic progression and impact of control measures. Decreasing the value of R 0 would decrease the proportion of total population infected by H1N1; however, the duration of the outbreak may be prolonged.